Interpretation and Overinterpretation of Ja’far Ibn Hasan Al-Barzanji’s Mawlid Al-Barzanji - Fadlil Munawwar Mashur (Humaniora, 2017)
This article examines the use of interpretation and overinterpretation in understanding Ja’far ibn Hasan al-Barzanji’s text, Mawlid al-Barzanji, one of the religious literatures in Indonesia. The results of the study indicate that Mawlid Al-Barzanji which contain majesty, miracles, prayer, and profound love for the Prophet is widely responded by Indonesian Muslims through the process of reading, interpretation, and appreciation. Such widespread acceptance is due to the fulfillment of interpretation requirements which requires the existence of a common world view between author and reader or interpreter. On the other hand, overinterpretation occurs when the text of Mawlid Al-Barzanji is interpreted by those who have different world views as a result of different religious ideas and religious ideologies. Such overinterpretation invites negative response, ideological prejudice, and rejection of some parts of Al-Barzanji text by those who identify themselves as a salafi group.